Bioeconomy and global inequalities: socio-ecological perspectives on biomass sourcing and production - Backhouse, Maria; Lehmann, Rosa; Lorenzen, Kristina; Lühmann, Malte; Puder, Janina; Rodríguez, Fabricio; Tittor, Anne (Palgrave Macmillan, 2021)
This open access book explores bioeconomy and bioenergy policies across South America, Asia and Europe. It discusses how a transition away from a fossil and towards a bio-based economic order alters, reinforces and challenges socio-ecological inequalities. A series of conceptual discussions and case studies with a multidisciplinary background in the social sciences illuminate how the deployment of biomass sources from the agricultural and forestry sectors affect societal changes concerning knowledge production, land and labour relations, political participation and international trade. How can a global perspective on socio-ecological inequalities contribute to a critical understanding of bioeconomy? Who participates in the negotiation of specific bioeconomy policies and who does not? To what extent does the bioeconomy affect existing socio-ecological inequalities in rural areas? What are the implications of the bioeconomy for existing relations of extraction and inequalities across regions? The volume is an invitation to reflect upon these questions and more, at a time when the need for an ecological and socially just transition away from a carbon intensive economy is becoming increasingly pressing.
Literaturangaben. - Index
Open Access unter: https://doi.org/10.1007/978-3-030-68944-5
"This edited volume entitled "Bioeconomy and Global Inequalities: Socio-Ecological Perspectives on Biomass Sourcing and Production" builds on an international workshop held between 25 and 27 June 2019 in Jena, Germany." - Seite v
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Fallstudie; Konferenzschrift; Energiepflanzenbau; Biomasseproduktion; Bioenergie; Bioenergieerzeugung